Manganese oxide magnetic nanoparticles and preparation method and application thereof

The preparation and modification of manganese oxygen magnetic nanoparticles by hydrothermal method of the autoclave reactor has solved the problem of difficult and high cost in preparing existing low Curie point anti-icing materials, and achieved nanoparticles with low Curie temperature and high heat generation levels, which are suitable for efficient anti-icing and frost protection for transmission wires.

CN118724070BActive Publication Date: 2025-04-29CHONGQING UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410969950.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-18
Publication Date
2025-04-29
Estimated Expiration
2044-07-18

AI Technical Summary

Technical Problem

The existing low Curie point anti-icing materials are difficult and costly, and operating at room temperature will increase the burden on transmission wires, making it impossible to quickly achieve wire deicing effects at low temperatures.

Method used

Manganese oxygen magnetic nanoparticles were prepared by hydrothermal method of the autoclave reactor. By adjusting the material composition and process parameters, manganese oxygen magnetic nanoparticles with particle size of about 300 nm were prepared, and their surfactivity and hydrophobicity were improved by modification of oleic acid and fluorosilane.

Benefits of technology

Manganese oxygen magnetic nanoparticles with low Curie temperature and low preparation cost have better heating level and anti-ice and frost performance, and are suitable for the preparation of anti-ice and frost materials for transmission wires.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118724070B_ABST
    Figure CN118724070B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of anti-icing materials, and particularly relates to a manganese ferrite magnetic nanoparticle, a preparation method and an application thereof. The molecular formula of the manganese ferrite magnetic nanoparticle prepared by the present invention is La x Ca y Sr z MnO3; wherein X = 0.1 - 0.7, Y = 0.1 - 0.35, Z = 0 - 0.16, and it is made of the following materials in parts by weight: 10 - 70 parts of lanthanum nitrate, 10 - 35 parts of calcium nitrate, 2 - 10 parts of strontium nitrate, and 30 - 50 parts of manganese nitrate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of anti-icing materials, and in particular relates to manganese oxide magnetic nanoparticles and a preparation method and application thereof. Background Art

[0002] Transmission line icing seriously threatens the safe operation of power systems, and my country is one of the countries with the most serious icing disasters on power lines. Currently, the commonly used methods for preventing and controlling icing of power lines include mechanical methods, natural passive methods, wire surface modification methods and thermal methods. Among them, the mechanical method can only reduce the disaster to a certain extent, but cannot prevent it. The natural passive method will cause line accidents such as wire jumping due to uneven or different periods of deicing. The surface modification method has no effect on ice formed by frost. Thermal deicing uses additional heat sources or the heat generated by the wire itself to prevent ice and snow from accumulating on the wire or to melt the accumulated ice and snow. There are three types of thermal deicing. The first is to pass a transmission current with a higher current density than the normal current density on the line to obtain heat to melt the ice. The second is to use resistive ferromagnetic wires. The third is to use low Curie point anti-icing materials. When low Curie point anti-icing materials are wrapped on the surface of the conductor, the de-icing principle is that when the ambient temperature drops below the Curie temperature of the material, the material generates a large magnetic induction intensity under the strong alternating magnetic field of the line, thereby generating heat to achieve anti-icing or de-icing effects. However, the current low Curie point anti-icing materials are difficult to prepare, the preparation cost is high, and there are few materials that meet the lower Curie temperature.

[0003] The patent with publication number CN105801099A (20160727) discloses a MnZn ferrite material with Curie point temperature sensitivity, which is prepared by means of multiple grinding and calcination of manganese oxide, zinc oxide, molybdenum disulfide powder, nano-titanium dioxide, polyethylene glycol, graphene, white carbon black, carbonyl iron powder, cobalt oxide, and tantalum trioxide. However, the composition of the material is relatively complex, the preparation process requires high requirements, and the minimum Curie temperature of the material is 26.8°C at room temperature. Under normal temperature power transmission, the material will generate magnetic induction heating, which will cause a long-term operating burden on the power transmission line at room temperature. In addition, the material cannot meet the requirement of rapid heating at low temperatures of ice to achieve the effect of wire deicing.

[0004] The patent with publication number CN117551317A (20240213) discloses a low Curie point polymer composite material and preparation method. The patent melts the random copolymer and mixes it with fatty alcohols and conductive fillers to prepare a polymer composite. The mechanism of the patented material for anti-icing is the electrothermal effect caused by the large resistance of the material.

[0005] The patent CN112552767A (20210326) discloses a low Curie point ferromagnetic anti-icing material suitable for conductors and a preparation method thereof. Specific weight portions of iron, nickel, silicon, chromium, cerium, and praseodymium-neodymium alloy are added to a vacuum induction melting furnace, and the melt is sprayed into a cooling tower under an argon atmosphere to obtain an atomized powder; the atomized powder is then blended with carbon black, xylene is added for high-speed stirring, and then fluoropolyacrylate and an antioxidant are added to prepare the material together. The low Curie point ferromagnetic anti-icing material prepared by this patent has a relatively complex composition and a high preparation cost.

[0006] In summary, it is necessary to propose new methods or strategies to prepare a material with low Curie point temperature and low preparation cost to alleviate the shortcomings of the existing technology. Summary of the invention

[0007] In view of this, the purpose of the present invention is to provide a low Curie point manganese oxide magnetic nanoparticle coating and a preparation method for use in the anti-icing field to alleviate or partially alleviate the deficiencies of the prior art. The specific technical solution is as follows.

[0008] A manganese oxide magnetic nanoparticle, wherein the molecular formula of the manganese oxide magnetic nanoparticle is La x Ca y Sr z MnO3; wherein X=0.1-0.7, Y=0.1-0.35, Z=0-0.16, comprising the following materials in parts by weight: 10-70 parts of lanthanum nitrate, 10-35 parts of calcium nitrate, 2-10 parts of strontium nitrate and 30-50 parts of manganese nitrate.

[0009] Furthermore, the invention is made of the following materials in parts by weight: 30-60 parts of lanthanum nitrate, 10-25 parts of calcium nitrate, 2-5 parts of strontium nitrate and 30-40 parts of manganese nitrate.

[0010] As a preferred embodiment, it is made of the following materials in parts by weight: 3 parts of lanthanum nitrate, 10 parts of calcium nitrate, 2 parts of strontium nitrate and 40 parts of manganese nitrate.

[0011] As a preferred embodiment, the molecular formula of the manganese oxide magnetic nanoparticles is La x Ca y MnO3; wherein X=0.3, Y=0.1.

[0012] Furthermore, the particle size of the manganese oxide magnetic nanoparticles is in the range of 50-300 nm.

[0013] Furthermore, the particle size range of the manganese oxide magnetic nanoparticles includes 50-100nm, 100-150nm, 150-200nm, 200-250nm or 250-300nm.

[0014] The method for preparing the above-mentioned manganese oxide magnetic nanoparticles is a high-pressure reactor hydrothermal method, and the specific steps are as follows:

[0015] S01: Add the following materials in parts by weight into pure water and stir to obtain a reaction solution: 10-70 parts of lanthanum nitrate, 10-35 parts of calcium nitrate, 2-10 parts of strontium nitrate and 30-50 parts of manganese nitrate,

[0016] The pH value of the reaction solution was adjusted to be alkaline, and further sonicated;

[0017] S02: adding the reaction solution of S01 into a high pressure reactor and heating at 200-300° C. for 12-24 hours;

[0018] S03: drying the product after the reaction, annealing it at 800-1200° C. for 4-24 hours, and grinding it to obtain a crude product of manganese oxide magnetic particles;

[0019] S04: modifying the crude manganese oxide magnetic particles to obtain the manganese oxide magnetic nanoparticles.

[0020] Furthermore, in S01, the pH value of the reaction solution is adjusted to 8-10.

[0021] Furthermore, the S03 is annealed at 900-1000° C. for 10-15 hours.

[0022] Further, the modification in S04 includes modification with oleic acid and / or fluorosilane. Specifically, modification with oleic acid, modification with fluorosilane, or modification with a mixture of oleic acid and fluorosilane.

[0023] Furthermore, the modification in S04 comprises adding the crude manganese oxide magnetic particles into oleic acid and / or fluorosilane and stirring at 60-90°C.

[0024] As a preferred embodiment, in S04, the crude manganese zinc ferrite nanoparticles are modified with 5%-25% oleic acid and 3%-20% fluorosilane.

[0025] Oleic acid modification produces organic active groups on the surface of oxide particles, which can be better combined with other organic coatings in the future. Further modification with fluorosilane produces -CF groups on the particles, which have a certain hydrophobicity and further improve the anti-frost performance.

[0026] The application of the above-mentioned manganese oxide magnetic nanoparticles in the preparation of low Curie point anti-icing coatings.

[0027] Beneficial technical effects

[0028] The present invention adopts a hydrothermal method to prepare a manganese oxide magnetic nanoparticle with a particle size of about 300nm and in the form of round particles. The manganese oxide magnetic nanoparticle has a low Curie temperature and a very small iron loss effect, and can be used to prepare anti-icing and anti-frost materials for power transmission lines. In addition, the manganese oxide magnetic nanoparticle has a maximum magnetic entropy change of 1.18J / kg K, which has a better heat generation level than the maximum magnetic entropy change value of 0.64-1.25J / kg K published in public data.

[0029] Secondly, the present invention modifies the prepared manganese oxide magnetic nanoparticles with oleic acid, fluorosilane or a combination of oleic acid and fluorosilane, so that the surface of the manganese oxide magnetic nanoparticles has active groups or exhibits hydrophobic properties, which can be better combined with other organic coatings to prepare anti-icing and anti-frost materials with low Curie point.

[0030] Finally, the hydrothermal preparation method adopted in the present invention is relatively simple to operate, has low equipment requirements, and has controllable overall costs, and is suitable for large-scale industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. In all the drawings, similar elements or parts are generally identified by similar reference numerals. In the drawings, each element or part is not necessarily drawn according to the actual scale. Obviously, the drawings described below are some embodiments of the present invention. For those of ordinary skill in the art, other drawings can also be obtained based on these drawings without paying creative labor.

[0032] Figure 1 This is a SEM image of manganese oxide magnetic nanoparticles prepared in one of the examples of the present invention without oleic acid modification (scale bar is 1 μm);

[0033] Figure 2 This is a SEM image of oleic acid-modified manganese oxide magnetic nanoparticles prepared in one of the examples of the present invention (scale bar is 300 nm);

[0034] Figure 3 This is an elemental composition analysis diagram of manganese oxide magnetic nanoparticles prepared in one embodiment of the present invention;

[0035] Figure 4 The control manganese oxide magnetic nanoparticles (A is La) prepared in one of the embodiments of the present invention 0.67 Ca 0.33 MnO3, B is La 0.7 Ca 0.25 Sr 0.05 MnO3, C is La0.6 Ca 0.35 Sr 0.15 MnO3);

[0036] Figure 5 The control manganese oxide magnetic nanoparticles (A is La) prepared in one of the embodiments of the present invention 0.67 Ca 0.33 MnO3, B is La 0.6 Ca 0.35 Sr 0.15 MnO3, C is La 0.1 Ca 0.1 MnO3);

[0037] Figure 6 This is an EDS image of manganese oxide magnetic nanoparticles prepared in one of the examples of the present invention modified by different means (A is OA modified, B is OA+FAS modified);

[0038] Figure 7 The Curie temperature test result of manganese oxide magnetic nanoparticles modified with oleic acid and fluorosilane prepared in one of the embodiments of the present invention;

[0039] Figure 8 The calculation result of magnetic entropy change of manganese oxide magnetic nanoparticles modified with oleic acid and fluorosilane prepared in one of the embodiments of the present invention;

[0040] Fig. 9 The thermogravimetric test results of manganese oxide magnetic nanoparticles modified with oleic acid and fluorosilane prepared in one of the embodiments of the present invention;

[0041] Fig.10 This is an anti-frost experiment of manganese oxide magnetic nanoparticles prepared in one of the embodiments of the present invention (A is an experimental sample, and B is a control sample);

[0042] Fig.11 The figure shows the iron loss effect measurement result of the manganese oxide magnetic nanoparticles prepared according to one embodiment of the present invention. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Herein "and / or" includes any and all combinations of one or more of the associated listed items.

[0045] Herein, "plurality" means two or more than two, ie, it includes two, three, four, five, etc.

[0046] It should be noted that, in this article, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises a ..." does not exclude the existence of other identical elements in the process, method, article or device including the element.

[0047] As used in this specification, the term "about" typically means + / - 5% of the stated value, more typically + / - 4% of the stated value, more typically + / - 3% of the stated value, more typically + / - 2% of the stated value, even more typically + / - 1% of the stated value, and even more typically + / - 0.5% of the stated value.

[0048] In this specification, some embodiments may be disclosed in a format of being within a certain range. It should be understood that such description of "being within a certain range" is only for convenience and brevity, and should not be interpreted as a rigid limitation on the disclosed range. Therefore, the description of the range should be considered to have specifically disclosed all possible sub-ranges and independent numerical values ​​within this range. For example, the range The description of should be considered to have specifically disclosed sub-ranges such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6 etc., as well as individual numbers within this range, for example, 1, 2, 3, 4, 5, and 6. The above rules apply regardless of the breadth of the range.

[0049] Example 1

[0050] This embodiment provides an example of a method for preparing manganese oxide magnetic nanoparticles.

[0051] Preparation method:

[0052] S01: Add the following materials in parts by weight into pure water and stir for 1 hour: 30 parts of lanthanum nitrate, 10 parts of calcium nitrate, 2 parts of strontium nitrate and 40 parts of manganese nitrate, adjust the pH value of the reaction solution to 9, and then ultrasonicate for 1 hour;

[0053] S02: The reaction solution of S01 was added into a high pressure reactor and heated at 270°C for 24h;

[0054] S03: drying the product after the reaction, annealing it at 1000° C. for 10 h, and grinding it to obtain a crude product of manganese oxide magnetic particles;

[0055] S04: Add the crude manganese oxide magnetic particles prepared in S03 to an ethanol or methanol solution and stir, further add 5%-25 oleic acid (OA) and 3%-20% fluorosilane (FAS), stir and heat to 60-90°C, remove ethanol or methanol, filter and dry to finally obtain the manganese oxide magnetic nanoparticles.

[0056] The molecular formula of the manganese oxide magnetic nanoparticles prepared in this example is La 0.3 Ca 0.1 MnO3, the crude particle size is about 50nm, after modification, the particle size is about 300nm, and the overall morphology is small particles. Figure 1 and Figure 2 , the overall spectrum of component analysis is shown in Figure 3 .

[0057] Example 2

[0058] This example provides a comparative preparation example based on Example 1.

[0059] (1) Based on the method of Example 1, by adjusting the material composition and not performing annealing, only a rod-like structure can be obtained.

[0060] Table 1 Nanoparticles prepared by different material ratios

[0061]

[0062] (2) Based on the method of Example 1, rod-like structures and granular structures are obtained by adjusting the material composition and performing annealing operations with different parameters.

[0063]

[0064] (3) The La prepared in Example 1 0.3 Ca 0.1 Based on the MnO3 nanoparticles, different methods were selected for modification, including oleic acid (OA) and oleic acid (OA) plus fluorosilane (FAS) modification, see Figure 6 After modification by the two methods, nanoparticles with a particle size of about 300 nm and an overall morphology of small particles can be obtained.

[0065] Example 3

[0066] This example provides performance verification of the modified manganese oxide magnetic nanoparticles prepared in Example 1.

[0067] 3.1 Curie temperature test

[0068] Method and steps: The SQUID-VSM magnetic measurement system of Quantum Design Company in the United States is used. The system is based on quantum superconducting interference device detection technology. By applying a DC or AC magnetic field to the magnetic material, the DC (AC) magnetization intensity of the sample to be tested changes with temperature (field strength) curves, that is, the measurement of MH and MT curves, is obtained. The MT curve is fitted with a straight line, and the temperature point with the largest slope is the Curie temperature point. The specific steps are as follows.

[0069] (1) Weigh the mass of magnetic powder.

[0070] (2) Load the magnetic powder sample into the instrument sample rod and place the sample rod into the sample chamber.

[0071] (3) Clean the cavity with helium (the program defaults to cleaning three times) and then evacuate it.

[0072] (4) Set the temperature (100K-400K) and magnetic field (1.5T), and determine the sample position by scanning the sample's "signal-position" curve.

[0073] (5) By applying a DC or AC magnetic field to the magnetic powder, the DC (AC) magnetization intensity of the sample to be tested changes with temperature (field strength) curve, that is, the MT curve measurement. The MT curve is fitted with a straight line, and the temperature point with the largest slope is the Curie temperature point.

[0074] Results: La modified with oleic acid and fluorosilane 0.3 Ca 0.1 The Curie temperature of MnO3 nanoparticles is about 264.50K, reaching a low temperature state (about -8.65℃). It meets the Curie point temperature requirement of about 0℃, see Figure 7 .

[0075] According to the above MT curve test results, the heating efficiency can be evaluated by calculating the magnetic entropy change at different temperatures through the formula referenced by public data, as follows Figure 8 As shown, the maximum magnetic entropy change of the material prepared by the present invention near the Curie temperature is 1.18 J / kg K, which has a better heat generation level than the maximum magnetic entropy change value of 0.64-1.25 J / kg K published in public data. The cited public data is Observation of the magnetic entropy change in Zndoped MnFe2O4 common ceramic: Be cool being environmentally friendly.

[0076] 3.2 Thermogravimetric test

[0077] Method and steps: Thermogravimetric analyzer (TGA) is used for detection. Under program temperature control (0°C to 1200°C, heating for 1 hour), the relationship between the mass of magnetic powder and temperature (or time) is measured, and the endothermic and exothermic processes in the process are measured.

[0078] Results: La modified with oleic acid and fluorosilane 0.3 Ca 0.1 MnO3 nanoparticles were subjected to thermogravimetric testing. Fig. 9 As shown, it is shown that the quality can be kept stable in the temperature range of 800-900℃.

[0079] Example 4

[0080] This example provides an anti-icing and anti-frost performance test of the modified manganese oxide magnetic nanoparticles prepared in Example 1.

[0081] Method and steps: Using semiconductor refrigeration platform LTD1-350, the sample was placed on the semiconductor refrigeration platform for frosting experiment at -8°C. La modified with oleic acid and fluorosilane prepared in Example 1 was placed on the semiconductor refrigeration platform 0.3 Ca 0.1 MnO3 nanoparticles and alcohol are mixed and coated on the surface of the super-hydrophobic pore structure sample. The sample is placed on a magnet with a magnetic field of 2600GS (smaller magnetic field). The dark part is the oxidized pore sample coated with magnetic particles, and the white part is the uncoated oxidized sample.

[0082] Fig.10 It can be seen that as time goes by, it can be found that the dark part can resist delayed frost formation, further improving the frosting effect of the super-hydrophobic pore structure. It is proved that the magnetic particles prepared by the present invention can effectively prevent frost. In contrast, the blank substrate sample has been completely frosted in 5 minutes, while the super-hydrophobic pore structure coated with magnetic particles can delay to 30 minutes.

[0083] It can be understood that the super-hydrophobic pore structure sample in this embodiment can be prepared according to any feasible method in the public information.

[0084] Example 5

[0085] This example provides an iron loss test of the modified manganese oxide magnetic nanoparticles prepared in Example 1.

[0086] Method and steps: The SQUID-VSM magnetic measurement system from Quantum Design, USA, was used. The specific steps are as follows.

[0087] (1) Weigh the mass of magnetic powder.

[0088] (2) Load the sample into the sample rod and place the sample rod into the sample cavity.

[0089] (3) Clean the chamber with helium (the program defaults to cleaning three times), and then evacuate. (4) Set the temperature (100K-400K) and magnetic field (1.5T), and determine the sample position by scanning the sample's "signal-position" curve.

[0090] (5) By applying a DC or AC magnetic field to the magnetic powder, the DC (AC) magnetization intensity of the sample to be tested is measured as a function of temperature (field strength), i.e., the MH curve. For the MH curve at each temperature, the value of H is calculated when M=0. The larger the absolute value of H, the greater the coercive force, which is more likely to cause heat generation under the alternating magnetic field of power transmission at room temperature, and thus iron loss. Similarly, the smaller the value of H or the closer the curves are to 0, the smaller the coercive force is, the better the paramagnetism is, and the less heat is generated under the alternating magnetic field at room temperature.

[0091] Results: La modified with oleic acid and fluorosilane 0.3 Ca 0.1 The coercivity of MnO3 nanoparticles at various temperatures of 260k, 270k, 280k, 290k and 300k is 0.4Oe, and the remanence is also very small and close to 0. It is determined to be a soft magnetic material, which will not cause hysteresis loss and heating effect under power transmission, and can be used for anti-icing or anti-frost of power transmission lines, see Fig.11 .

[0092] The embodiments of the present invention are described above in conjunction with the accompanying drawings, but the present invention is not limited to the above-mentioned specific implementation modes, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can also make many forms without departing from the scope of protection of the present invention and the claims, all of which are within the protection of the present invention.

Claims

1. A method for preparing manganese oxide magnetic nanoparticles, characterized in that: The method is a high-pressure reactor hydrothermal method, and the specific steps are as follows: S01: Add the following materials in parts by weight into pure water and stir: 30-60 parts of lanthanum nitrate, 10-25 parts of calcium nitrate, 2-5 parts of strontium nitrate and 30-40 parts of manganese nitrate, adjust the pH value of the reaction solution to 8-10, and further perform ultrasound; S02: adding the reaction solution of S01 into a high pressure reactor and heating at 200-300° C. for 12-24 hours; S03: drying the product after the reaction, annealing it at 900-1000° C. for 10-15 hours, and grinding it to obtain a crude product of manganese oxide magnetic particles; S04: modifying the crude manganese oxide magnetic particles to obtain the manganese oxide magnetic nanoparticles; the modification includes modification with oleic acid and / or fluorosilane; the molecular formula of the manganese oxide magnetic nanoparticles is La x Ca y MnO3; wherein X=0.3, Y=0.

1.

2. The preparation method according to claim 1, characterized in that The modification in S04 comprises adding the crude manganese oxide magnetic particles into oleic acid and / or fluorosilane and stirring at 60-90°C.

3. The preparation method according to claim 1, characterized in that: The particle size range of the modified manganese oxide magnetic nanoparticles in S04 is 250-300nm.

4. Use of manganese oxide magnetic nanoparticles prepared by the preparation method according to any one of claims 1 to 3 in the preparation of low Curie point anti-icing coatings.

Citation Information

Patent Citations

  • MnZn ferrite with curie point temperature sensitivity and preparation method

    CN105801099A

  • Low-curie-point ferromagnetic anti-icing material suitable for wire and preparation method thereof

    CN112552767A

  • High-molecular composite material with low curie point and positive temperature coefficient as well as preparation method and application of high-molecular composite material

    CN117551317A

  • Perovskite manganese oxide porous nanosphere as well as preparation method and application thereof

    CN115353149A